Estágio Profissional: O percurso de desenvolvimento profissional de um estudante estagiário. - Duarte Nuno Lobo Gonçalves Bandeira (2021)
This report presents the work done throughout the internship in Physical Education Teaching in Basic and Secondary Education developed in a grouping school, guided by a guiding teacher (GT) of the faculty and a cooperative teacher (CP) of the cooperative school. This final report will present all the work developed defined in the programmatic lines of supervised teaching practice (PES). The added value and difficulties encountered during this period will be mentioned, an analysis that shows the evolution operated in the student from the beginning of the internship to its completion. During the school year, there were several constraints since, from the 2nd school period, classes ceased to be in- person and started to be online, and the school calendar was changed, which led to the reformulation of all programming work already done. This embarrassment (pandemic) motivated the creation of a project, encourage by the internship nucleus, entitled ''wins by the class''. This project aimed students to develop motor skills related to various modalities and psychosocial behaviors, although the pandemics obstacles inhibited them from significant physical contact. Thus, my research project was born, constant in area 3 of this work, with the title: ''Educational impact of students participation in the project ''wins by the class'''', where it is intended to investigate the impact of the project on the training of students. In addition to this study, this internship report gives an account of everything that was done during distance learning and the strategies and difficulties inherent in this type of teaching, which was unexpected and gave me the ability to adapt and be creative. The different items covered in this document should be seen to achieve an end: the training and evolution of a physical education teacher.